The Impact of a Mindfulness-Based Intervention on Developing Health Behavior and Reducing Death Anxiety among Cardiac Patients: A Quasi-experimental Study - Al-Dalaeen, Anas Saleh; Alzaben, Mamduh Baniah Lafee; Al-Takhayneh, Suhaib khaled (Dirasat: Educational Sciences, 2024)
Objectives: This study examines the effectiveness of mindfulness-based intervention in fostering healthy behaviour and reducing death anxiety among cardiac patients in Jordan. Methods: To achieve the research objectives, scales were developed to evaluate healthy behavior and death anxiety. Furthermore, the mindfulness-based intervention guidence program is designed and administered. A sample of 21 heart patients was purposefully selected and distributed into two groups: an experimental group of (11) patients who underwent the mindfulness-based guidene program and a control group of (10) patients who did not receive any intervention. The mental intervention was performed for a month and a half with the experimental group. Results: The results demonstrated significant improvements in healthy behaviour, and a decrease in death anxiety among participants in the experimental group compared to those in the control group. Furthermore, follow-up assessments revealed that these beneficial effects were sustained in the experimental group. Conclusions: The study supports focusing on mindfulness-based intervention as a therapeutic approach to enhance healthy behavior and reduce death anxiety among heart patients. The researchers conclude that heart patients need such interventions to improve their quality of life, and to positively reflect on their psychological wellbeing.